Celebration of Maha Shivaratri - Mumbai Archive Project Team (Jio Institute, 2024)
According to Hindu mythology, Maha Shivaratri marks the day when Lord Shiva performed the cosmic dance, Tandava, and the night he married Parvati. In Maharashtra, the festival is observed with large gatherings in temples, fasting, and night-long vigils.